Ponowoczesna wizja Powstania Warszawskiego w filmie Jana Komasy Miasto 44 - Lewandowska, Zuzanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
The Postmodern Vision of the Warsaw Uprising in Jan Komasa’s City 44 City 44 (2014) by Jan Komasa presents an original vision of the Warsaw Uprising – especially when compared to other historical productions. Both formal aspects of the film and the way its presents the uprising expose its postmodern character. Th e conclusion that City 44 can be interpreted by means of key postmodern concepts is based on an analysis of its visual aspects, such as scenes operating at the edge of realism and aff ectation, and aesthetic denominators taken from all genres, as well as pop culture references, intertextuality, and the subjective vision of the uprising based on the story of two main protagonists.